Deferitazole, a new orally active iron chelator. Issue 11 (17th February 2015) - Hider, Robert C.; Kong, Xiaole; Abbate, Vincenzo; Harland, Rachel; Conlon, Kelly; Luker, Tim
Abstract : Deferitazole possesses a high affinity and selectivity for iron(iii ), forming an equilibrium mixture of two Fe III (deferitazole)2 complexes, under biological conditions. Abstract : Following a systematic search of desferrithiocin analogs, a polyether derivative, deferitazole (formerly FBS0701), has entered into phase 1 and 2 clinical trials with promising biological properties. However, until now, detailed physicochemical properties of this chelator have not been reported. The compound displays a high affinity and selectivity for iron(iii ) as demonstrated by the log  β 2 = 33.39 ± 0.03 and the pFe 3+ value of 22.3. Two equilibrating isomeric forms of the iron(iii ) complex exist under biological conditions. Deferitazole also binds the trivalent metals Al III and La III with high affinity; log  β 2 values, 26.68 and 21.55 respectively. The affinity of deferitazole for divalent cations is somewhat lower, with the exception of Cu II which possesses a log  β 2 value of 25.5; deferitazole scavenges iron from labile sources such as citrate and albumin with efficiencies comparable with those of other therapeutic iron chelators, including deferasirox, deferiprone and desferrioxamine. The Fe III (deferitazole)2 is stable under physiological conditions and does not redox cycle. The high affinity of deferitazole for iron(iii ) renders it unlikely that this chelator will lead to the redistribution of iron and consequently deferitazole shows considerable promise as a therapeutic iron(iii ) chelator.